Radverkehr und Verkehrswende. Eine Geschichte von Gegenwind und Rückenwind. - Bracher, Tilman (My University, 2021)
Im Zuge der Corona-Pandemie steigen immer mehr Menschen aufs Fahrrad, und auch die Klimapolitik setzt - neben technischem Fortschritt und öffentlichen Verkehrsmitteln - auf den Beitrag des Radverkehrs zur Verkehrswende. Mit dem Auto verbinden sich Wohlstand und Mobilität, aber die Klimaziele lassen sich ohne Verkehrswende nicht erreichen. Seit 2013 fördert das Bundesumweltministerium mit seiner "Nationalen Klimaschutzinitiative" auch kommunale Radverkehrsinvestitionen, und dank des Handlungsdrucks im Klimaschutz verfügt alleine das Bundesverkehrsministerium von 2020–2023 für den Radverkehr über 1,4 Mrd. Euro an Fördermitteln. Aber in den Kommunen fehlt es an umsetzbaren Projekten, weil dafür der Wille oder der Platz fehlt, weil das Straßenverkehrsrecht und andere Normen Projekte blockieren, die die Leichtigkeit des Autoverkehrs beeinträchtigen könnten und Parkplätze oder Fahrspuren kosten. Vielerorts fehlt es an Personal, um Fördermittel zu beantragen, und den notwendigen Eigenmitteln, Radverkehrsinvestitionen zu planen und umzusetzen. Trotzdem war die Zeit für den Radverkehr nie so günstig: Es gibt Handlungsdruck, Fördermittel, Wertewandel, Innovationen und immer mehr Beschlüsse und Konzepte. Der Band umreißt das verkehrspolitische Potenzial des Radverkehrs insbesondere auf kommunaler Ebene - und ist ein nachdrückliches Plädoyer für die Verkehrswende.

Anyone wishing to explain cycling policy in the 40-year period between 1981 and 2021 and wanting to venture a look into the future also needs to understand the beginnings of cycling. Karl-Friedrich von Drais is credited with being the father of the bicycle, although he actually only invented a balance bike with handlebars. The first pedalpowered bicycles with pneumatic tyres did not make an appearance until around the time the Eiffel Tower was built for the Paris World Fair in 1889. They were first used by the wealthy as a piece of sports equipment, but by the turn of the 20th century had already become both more affordable for the broader masses and an everyday means of transport. Cycling clubs were founded, even workers could afford to buy themselves a bike, there were cycling corps in the military and bicycles contributed to women’s emancipation. Along with trams and railways, bicycles helped launch the revolution in speed in towns and cities. For ease of travel, the first cycleways were built on the sand and large cobblestone roads which were typical of the German Imperial Era and also used by riders and carriages. They were either tracks running down the middle of the carriageway or lanes on the edge of the roadway – although these were increasingly obstructed by stationary cars or carriages. Later, raised cycleways along the side of the road also became common. When the cycling boom began in the early 20th century, the first towns and cities in Germany – including Magdeburg, Hanover and Munich – began building cycleways next to the carriageway. After the National Socialists seized power and in speeches by Adolf Hitler in 1933 and 1934, motor vehicles were declared a national symbol. After that even cycle path planners were eager to rid the roads of bothersome cycles, for the benefit of vehicle traffic. When the Reich Road Traffic Regulations entered into force in 1934, cyclists were then required to ride on the far right-hand side of the road, in single file, and to comply with the legal obligation to use cycle paths. The states and provinces were called to build cycle paths so as to get the vexatious bicycles off the road, but there was not enough time to do so before the Second World War broke out. The legal obligation to use cycle paths, which initially served the interests of automobile traffic and was later justified citing cycle traffic safety, remained enshrined in the Road Traffic Regulations from 1934 to 1998 – though it appears that many people think it was never abolished. Today, the obligation to use a cycle path can only be imposed where there is sufficient space for pedestrians and it is necessary for road safety reasons or to ensure the smooth flow of traffic. Anyone who cycles on a road although there is a cycle path (which they are not obliged to use) is often hooted at and intimidated by drivers as though the obligation still applied.
Cycling and the transport transition. A tale of headwinds and tailwinds.
Keywords: Verkehrswende; Straßenverkehr; Stadtverkehrsplanung; Fahrradverkehr; Verkehrspolitik; Verkehrsgeschichte; Radverkehrsförderung